A study and evaluation of client dropout at a drug counsellling centre in Cape Town - Rogers, Catherine Anne (Department of Social Development, 2016)
This study is motivated by the fact that half the clients attending a drug counselling centre in Cape Town, dropped out of treatment before the fourth interview. The study examines and describes the factors which contribute towards this dropout behaviour. Literature describing dropout behaviour and patterns of illicit drug abuse identified multiple factors influencing dropout behaviour. The present study utilizes four such categories: a) motivation factors, which include the pressure that families or employers exert on clients to attend treatment; b) client factors, including aspects of demography, symptomology and personality; c) treatment factors, such as evaluation methods, the initial contact, client expectations of the agency and treatment effectiveness; and d) therapist factors including therapist attributes, contracting and response to dropout behaviour. In order to explore factors contributing to dropout behaviour, an initial sample of 32 subjects was selected of which fourteen were interviewed by means of a structured questionnaire. An analysis of the results gives rise to the following important findings: Families do not influence the dropout to continue with treatment. Dropouts tend to have unrealistic treatment expectations, such as immediate medical relief from drug related symptoms. Dropouts also tend to have lower educational status and are more frequently employed in relation to the average client. The dropouts experience anxiety during the initial contact, which is often met by uncaring therapist attitudes. Finally, the study demonstrates that inflexible agency hours and a lack of therapist contracting also contribute toward dropout behaviour.